POPULATION DYNAMICS AND EXPLOITATION PARAMETERS OF CALLINECTES AMNICOLA (ROCHEBRUNE, 1883) IN THE LAGOON COMPLEXES OF SOUTH BENIN, WEST AFRICA - LALEYE, PHILIPPE A.; LEDEROUN, DJIMAN (My University, 2023)
To ensure the sustainable management of fisheries resources in Benin, the population dynamics of Callinectes amnicola are being studied in two locations: the lake Nokoué-Porto-Novo lagoon complex and the lake Ahémé-Coastal lagoon complex. Monthly recordings of carapace length were conducted on 5,850 crabs from lake Nokoué-Porto-Novo lagoon complex between February 2017 and January 2018, while 2,252 crabs from lake Ahémé-Coastal lagoon complex were analyzed using FiSAT II software to determine population dynamics parameters. The estimated asymptotic carapace lengths (L∞) were found to be 14.70 cm and 17.85 cm for lake Nokoué-Porto-Novo lagoon complex and lake Ahémé-Coastal lagoon complex, respectively. The growth rate (K) was calculated as 3.1 for lake Nokoué-Porto-Novo lagoon complex and 0.63 for lake Ahémé-Coastal lagoon complex. Estimates of fishing mortality (F) were determined as 6.97 year−1 for lake Nokoué-PortoNovo lagoon complex and 0.66 year−1 for lake Ahémé-Coastal lagoon complex. The size at first capture was estimated to be 11.87 cm for lake Nokoué-Porto-Novo lagoon complex and 11.20 cm for lake Ahémé-Coastal lagoon complex. The current exploitation rates were found to be 0.60 for lake Nokoué-Porto-Novo lagoon complex and 0.3 for lake Ahémé-Coastal lagoon complex. These findings indicate that the stock of Callinectes amnicola is overexploited in lake Nokoué-Porto-Novo lagoon complex, while in contrast, it is not overexploited in lake Ahémé-Coastal lagoon complex. The stocks in lake Nokoué-PortoNovo lagoon complex have reached a critical level of overexploitation. Therefore, it is necessary to reduce the level of species exploitation in this complex while respecting the optimal carapace length.
Keywords: Coastal lagoon; Crab; lake Ahémé; lake Nokoué; Porto-Novo lagoon.